2015
DOI: 10.1177/003335491513000416
|View full text |Cite
|
Sign up to set email alerts
|

Change in Population Characteristics and Teen Birth Rates in 77 Community Areas: Chicago, Illinois, 1999–2009

Abstract: The study provides a model of census-based measures that can be used to evaluate predicted vs. observed rates of change in teen births across communities, offering the potential to more appropriately prioritize public health resources for preventing unintended teen pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…One found that an increased proportion of adults 25 or older with a college education within a zip code was associated with a decreased adolescent birthrate among all racial groups (Kirby et al, 2001). Two other studies (Blake and Bentov, 2001;Gunaratne et al, 2015) found that an increased proportion of adults 25 or older with lower education levels was positively correlated with higher birthrates. Qualitative results from Decker et al (2016) revealed that communities with higher adolescent birthrates were more likely to perceive fewer available educational opportunities.…”
Section: Adolescent Birthratementioning
confidence: 99%
See 3 more Smart Citations
“…One found that an increased proportion of adults 25 or older with a college education within a zip code was associated with a decreased adolescent birthrate among all racial groups (Kirby et al, 2001). Two other studies (Blake and Bentov, 2001;Gunaratne et al, 2015) found that an increased proportion of adults 25 or older with lower education levels was positively correlated with higher birthrates. Qualitative results from Decker et al (2016) revealed that communities with higher adolescent birthrates were more likely to perceive fewer available educational opportunities.…”
Section: Adolescent Birthratementioning
confidence: 99%
“…Three studies used neighborhood geographic boundaries defined by community members, referenced in Table 2 as "participant defined neighborhoods". Two studies used governmental definitions specific to the location, "community areas" in Chicago and "Medical Service Study Areas" in California (Gunaratne et al, 2015;Decker, 2016). Some researchers parceled neighborhood clusters to achieve relative population homogeneity in racial/ethnic, socioeconomic, and housing structure characteristics.…”
Section: Definitions Of Neighborhoodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most prior studies on teen pregnancy and birth focus on individual-and interpersonal-level risk factors and prevention programmes emphasizing knowledge and personal decision-making rather than contextual influence on teen pregnancy (Maness and Buhi, 2016). Still, identification of contextual risk factors related to TBR, as well as its geographical distribution, is important in providing clues to causal pathways of increasing gaps in TBRs among regions (Salazar et al, 2010;Gunaratne et al, 2015). Some sociological theories have suggested possible explanations regarding spatial heterogeneity in TBRs (Shaw and McKay, 1969;Shoff and Yang, 2012).…”
Section: Introductionmentioning
confidence: 99%